Special Recurrent Transformation in an NPR-Finsler Space - Anjali Goswami (Cubo, 2012)
In this paper, an infinitesimal transformation , where the vector vi is recurrent has been considered in an NPR- Finsler space. Such transformation is being called special recurrent transformation if the recurrence vector of the NPR- Finsler space is Lie invariant. Besides different properties of such transformation, the conditions for such transformation to be curvature collineation and an afine motion have been obtained. En este artículo se considera una transformación infinitesimal , donde el vector v i es recurrente, en un espacio NPR- Finsler. Tal transformación se dice transformación recurrente especial si el vector recurrente del espacio NPR- Finsler es Lie invariante. Además se han obtenido diferentes propiedades de dicha transformación y las condiciones para que ésta sea una colineación de curvatura y una moción afín.